Piezoresistive Sensors Based on Electrospun Mats Modified by 2D Ti3C2Tx MXene - Patrik Sobolčiak; Aisha Tanvir; Kishor Kumar Sadasivuni; Igor Krupa (Sensors, 2019)
The preparation methodology and properties of electroconductive, electrospun mats composed of copolyamide 6,10 and Ti3C2Tx are described in this paper. Mats of several compositions were prepared from a solution of n-propanol. The obtained electrospun mats were then tested as piezoresistive sensors. The relative resistance (AR) of the sensor increased with an increase in the Ti3C2Tx content, and materials with relatively higher electrical conductivity displayed noticeably higher sensitivity to applied pressure. The pressure-induced changes in resistivity increased with an increment in the applied force.